2011
DOI: 10.1073/pnas.1007065108
|View full text |Cite
|
Sign up to set email alerts
|

Aphids alter host-plant nitrogen isotope fractionation

Abstract: Plant sap-feeding insects and blood-feeding parasites are frequently depleted in 15 N relative to their diet. Unfortunately, most fluid-feeder/host nitrogen stable-isotope studies simply report stable-isotope signatures, but few attempt to elucidate the mechanism of isotopic trophic depletion. Here we address this deficit by investigating the nitrogen stable-isotope dynamics of a fluidfeeding herbivore-host plant system: the green peach aphid, Myzus persicae, feeding on multiple brassicaceous host plants. M. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 45 publications
6
34
0
Order By: Relevance
“…These authors suggest that possible signals present in the salivary secretions of the aphid trigger the increase in nitrate reductase activity in cabbage leaf. Data presented here are consistent with the Wilson et al (2011) Glyma05g26390 -5.35 0.01 AT1G48100 Pectin lyase-like superfamily protein…”
Section: Analysis Of Differentially Expressed Genessupporting
confidence: 76%
See 1 more Smart Citation
“…These authors suggest that possible signals present in the salivary secretions of the aphid trigger the increase in nitrate reductase activity in cabbage leaf. Data presented here are consistent with the Wilson et al (2011) Glyma05g26390 -5.35 0.01 AT1G48100 Pectin lyase-like superfamily protein…”
Section: Analysis Of Differentially Expressed Genessupporting
confidence: 76%
“…Transcripts for this gene were significantly (-2.3-fold) down-regulated in the tolerant plants and significantly up-regulated (3.2-fold) in the susceptible plants. Aphid feeding can lead to a 2-fold increase in nitrate reductase activity in cabbage seedlings infested with the green peach aphid (Myzus persicae) (Wilson et al 2011). These authors suggest that possible signals present in the salivary secretions of the aphid trigger the increase in nitrate reductase activity in cabbage leaf.…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…However, this study documented that cotton aphids were only 0.5‰ enriched in 15 N relative to their hosts (cotton) and even maize aphids were more than 5‰ depleted in 15 N relative to their hosts (maize). The result was similar to the green peach aphid, Myzus persicae, which was more than 6‰ depleted in 15 N relative to their hosts (cabbage seedlings) (Wilson et al, 2011). Aphids are plant sap-feeding insects, which have been frequently reported as showing no enrichment or even depletion in 15 N relative to their diet (McCutchan et al, 2003;Sagers and Goggin, 2007;Schumacher and Platner, 2009;Scrimgeour et al, 1995).…”
Section: Prey Origins Of Predatory Beetlessupporting
confidence: 55%
“…2011; Wilson et al, 2011;Nalam et al, 2012). We observed that the vascular sap obtained from Tx601 plants that were previously infested with aphids had less antibiotic factors, suggesting that CLA were able to suppress defenses in Tx601 plants.…”
Section: Discussionmentioning
confidence: 64%